DEVELOPMENT OF MULTIMEDIA-DIGITAL IN EARLY CHILDREN LEARNING AT PAUD AL-IRSYAD AL ISLAMIYAH JEMBER - Yeni Rofiah; Nurul Anam (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
Digital multimedia is an important learning component. The current educational process should take advantage of multimedia-digital technology which has developed a lot in the world of education. The institute of PAUD Al-Irsyad Al Islamiyyah Jember strive to make this happen Therefore, the purpose of this study was to determine the development of digital multimedia in early childhood learning on the theme